Effect of oilseed sources and L-carnitine administration on growth, feed intake, feed digestibility, and blood metabolites of Afshari lambs - Borhani, M.; Foroozandeh, A. D.; Nasrollahi, S. M.; Amini, H. R. (Cuban Journal of Agricultural Science, 2016)
The experiment was conducted to evaluate the effects of oilseed sources and L-carnitine supplementation on growth, feed digestibility, and blood metabolites in Afshari lambs. Twenty male lambs of 2-month old and weighing 22.5 ± 2.58 kg were used in a completely randomized design with a 2×2 factorial arrangement (n=5) of oilseed sources with and without supplemental carnitine in an 84-day feeding period. Diets were isoenergetic and isonitrogenous. Soybean or canola seeds were included at 15% of the dry matter (DM) of the diet, each with or without 0.11 g/day L-carnitine applied to each lamb. Initial weight was stratified across dietary treatments. At the end of the experiment, serum glucose, ammonia, total protein, triglyceride, total cholesterol, HDL, and LDL were determined. There was no interaction between oilseed sources and L-carnitine level on feed intake, digestibility, or blood metabolites. Replacing soybean seed with canola seed and carnitine administration had no effects on feed intake, body weight gain, or feed conversion ratio. L-carnitine administration decreased (P≤0.05) NDF digestibility from 63.0 to 41.5% and tended to decrease (P=0.13) organic matter digestibility. Oilseed sources had no effects (P>0.05) on blood profile, but triglycerides and cholesterol tended (P=0.13) to be increased when soybean seeds were replaced with canola seeds. Although L-carnitine administration increased blood ammonia and tended to increase HDL (P=0.13), other blood metabolites were not affected. The results indicate that soybean seed could be substituted by canola seed in the diets of growing lambs. Supplementing with L-carnitine had no effect on responses of lambs fed diets of soybean seed and canola seed. Keywords: L-carnitine, canola seed, soybean seed, Afshari lamb, digestion, growth